Penerapan Media Pembelajaran Interaktif Sistem Tata Surya Di Kelas Vi Sdn Leuwiranji 03 - Nadia Farah Annisa; Risa Amalia Febrianti; Reza Primatama (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2021)
This research was conducted to describe how the application of interactive learning media in learning the solar system teaching materials for class vi thematic books at sdn leuwiranji 03 was applied by researchers. This study also describes how the responses or responses from students in carrying out the learning process using interactive learning media. This research is descriptive qualitative research. The subjects in this study were students who carried out learning using learning media. The object of research is focused on the application of interactive learning media for the solar system and the responses of students in the application, in terms of media design, and students' understanding after carrying out the learning process. Collecting data using observation techniques, questionnaires, and document analysis. In analyzing the data using qualitative descriptive analysis techniques. The results of the study show how the application of interactive learning media "solar system" to class vi students at sdn leuwiranji 03 is classified as good and successful, it can be seen from the criteria for fulfilling the implementation of the learning steps and can also be seen from the scores generated by students. In addition, the responses and responses of students were positive during the learning process. In the questionnaire that was distributed to assess the design of the media display, it was quite good.